CONSTITUCIONALISMO SOCIAL: DIREITO FUNDAMENTAL DO TRABALHADOR AO LEVANTAMENTO DO FGTS NA PANDEMIA DO COVID-19 PARA ALÉM DAS HIPÓTESES DA MP nº 946/20. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
ABSTRACT: In the context of the COVID-19 pandemic recognized through Legislative Decree No. 06/20, among a set of legal measures adopted within the scope of labor regulations, MP No. 946/20, in art. 6, admits the hypothesis of partial withdrawal of land deposits (FGTS), in the amount of R $ 1,045.00 (one thousand and forty-five reais), in active and inactive accounts, using the legal diction “stays available”, which allows to glimpse the option for the presumption of an economic “state of need”, for the evidence of the adverse economic effects resulting from the partial paralysis of the economic activities by the measures of social isolation, reaching indiscriminately the workers of diverse economic contexts, in formal or informal market, presumably under-sufficient , or hypersufficient (art. 444, sole paragraph, of the CLT with wording by Law No. 13,467 / 17). However, there is legal treatment for these exceptional situations in art. 20, item XVI, of Law 8,036 / 90, which will allow a hypothesis of interpretation according to the constitution, since it is predominantly a fundamental right of the worker enrolled in art. 7, section III of the Constitution, especially for the purposes of full lifting of inactive accounts, not excluding the legal nature of deferred pay, and to integrate the amount deposited the legal heritage of the worker.